Ameliorating effect of zinc on water transport in rice plants under saline-sodic stress - Dang, Kun; Tian, Hao; Bai, Jingjing; Fu, Pengcheng; Cui, Jiehao; Ji, Dongming; Shao, Xiwen; Geng, Yanqiu; Zhang, Qiang; Guo, Liying (Frontiers in Plant Science, 2025)
Saline-sodic stress not only impacts the absorption of nutrient ions, such as Zn2+, in rice but also induces physiological water shortages and ion toxicity in rice plants, significantly hindering their growth. To investigate this phenomenon, the present study utilized two rice varieties, ‘Changbai 9’ and ‘Tonghe 899’, as test subjects to simulate conditions of saline-sodic soil stress. Four-week-old rice seeds under four treatments: control (CT), 2 μmol L-1 zinc treatment alone (Z), 50 mmol L−1 saline-sodic treatment (S), and 50 mmol L−1 saline-sodic treatment with 2 μmol L-1 zinc (Z+S). The study aimed to examine the effect of zinc on water transport in rice plants under conditions of saline-sodic stress. Research indicates that the application of zinc positively influences the growth of rice under saline-sodic stress.The application of zinc not only reduces the Na+/K+ ratio and malondialdehyde (MDA) content, but also increases the levels of Zn2+, Cu2+, and other ions. Additionally, it enhances the expression of aquaporins in the plasma membrane of rice roots, which in turn increases the hydraulic conductance of the roots and ultimately improves the water absorption capacity of the root system under stress conditions. Additionally, zinc application promotes auxin (IAA) synthesis, facilitating root growth and expanding the root absorption area, which in turn enhances the water absorption rate and helps maintain higher leaf water content. Moreover, zinc application regulates stomatal conductance through an increase in potassium ion concentration and abscisic acid (ABA) content, thereby elevating the transpiration rate of rice leaves and promoting water absorption and transportation within the rice plants. Therefore, the addition of zinc under saline-sodic stress not only alleviates the effects of such stress but also enhances water absorption and transportation in rice plants. This results in a higher water content within the plants, positively influencing their growth and development under saline-sodic conditions.